The use of augmented reality to educate preschoolers on preventing dental malocclusion - Salim, Yulita; Puspitasari, Yustisia; Azis, Huzain; Anas, Risnayanti (Association for Scientific Computing Electrical and Engineering, 2019)
According to the World Health Organization (WHO), malocclusion is a deviation in dentofacial growth or an abnormal relationship between the teeth of both arches, which results in impaired physical function for sufferers. Causes of malocclusion include genetic factors, inappropriate growth and development processes, bad habits of children, and malnutrition. Also, malocclusion can be caused by a lack of knowledge of children, parents, and guardians of students in the school environment in maintaining oral health. Nurul Falah Kindergarten, located in Mamajang District in the middle of Makassar City. However, students in kindergarten are from the middle to lower economies with a lack of dental and oral health awareness. According to the principal, some students come with the condition of not brushing teeth and with cavities. This service activity aims to help solve the problems faced by teachers in pre-school age students by providing dental education based on Augmented Reality and Topical Application Fluor (TAF) as an effort to prevent malocclusion. It is hoped that through this activity malocclusion prevention can be done through promotive efforts on dental health. This dental extension will be complemented by the utilization of information technology advances in the form of android-based Augmented Reality (AR) technology that is able to visualize an object in 3 dimensions so that the counseling process becomes more interactive and real.